Mapping cavities of despondency: waiting as resistance in Niyi Osundare's Waiting Laughters. Issue 4 (1st October 2016) - Akingbe, Niyi
ABSTRACT: Commencing within the trajectory of perseverance, this paper sets out to examine the ways in which the phenomenon of waiting has been shrewdly explored by Niyi Osundare in Waiting Laughters [Osundare, N. (1990). Waiting laughters . Lagos: Malthouse]. Waiting is considered in the context of contemporary African literature and the poet's own Yoruba tradition. It goes on to argue that the poet extends meanings of waiting far beyond their conventional limits, thus making it a complex, multi-levelled construct deployed as an instrument of resistance in the face of deplorable socio-economic and political conditions of contemporary African states. The paper identifies several manifestations of waiting: as patience, as natural progression, as social predicament, as historical inevitability, as humour, as laughter therapy, and as resistance. Each of these notions of waiting is an element of Osundare's preoccupation with ways of overcoming the inequities, deprivations and injustices of African nations, and thus offers strategies for minimizing the effects of oppression.